Familial occurrence of bipolar disorder – case reports - Karakuła, Hanna; Perzyński, Adam; Szymona, Kinga; Kaczyńska-Haładyj, Maria; Kalinowska-Tomala, Joanna; Krukow, Paweł; Krasowski, Tomasz; Wcisło, Beata (Current Problems of Psychiatry, 2012)
Introduction. Bipolar Affective Disorder (BD) is a chronic mental illness afflicting approximately 1.5% of the population. A genetic contribution to the aetiology of this disorder is well-documented and estimated to be between 70and80%. In the case of familial occurrence of BD, an earlier onset is observed with a more severe course of the disease and poorer short- and long-term diagnosis.Aim and method. This paper presents a case report of a 17-year old patient of the Adolescent Unit at the Department of Psychiatry Medical University in Lublin, from a family where BD has been transmitted for over three generations. In order to make the presentation clear, the case report is organized under the three following sections: 1. Socio-demographic characteristics of the patient; his psychomotor development in childhood before the disorder developed; family history of mental disorders, 2. The course of BD in the first-degree relatives (father) and second-degree relatives (grandmother) 3. The course of BD in the patient.Conclusions: 1. Clear familial transmission of BD is associated with an earlier onset and more severe course of the disease as well as a poorer response to drug treatments. 2. Specialist care should be provided as early as during the prenatal period to monitor fetal development until birth in order to minimalize environmental factors contributing to the etiopathogenesis of BD and also to introduce early therapeutic interventions in the case of early symptoms.